Intended Nationally Determined Contributions in the Caribbean : Where does agriculture fit? - García, Mariana (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The Inter-American Institute for Cooperation on Agriculture (IICA) is pleased to present this publication, which synthesizes how agriculture is addressed in the INDCs of the Caribbean region. Together with its partners, IICA has been working for several years to promote a more active and informed participation of the agriculture sector in the international climate negotiations and national planning processes. The Institute stands ready to support its member states as needed in following up on their INDC commitments such as strengthening capacity to fully integrate climate change considerations into the plans and actions the sector undertakes; developing public policy frameworks; providing guidance to assess agricultural adaptation needs; and promoting intersectoral collaboration to maximize the synergies and co-benefits of mitigation and adaptation actions.